Response of cylindrical tubes subjected to internal blast loading. (1st December 2022) - Li, H.J.; Shen, C.J.; Lu, G.; Wang, Z.H.
Highlights: The dynamic response of the single walled and sandwich walled tubes subjected to an internal explosion was investigated. An empirical formula was presented to predict the deformation or failure of a tube under the internal explosion. An analytical model was proposed to describe the response of the sandwich tube under the internal blast loading. Abstract: Cylindrical metallic tubes are commonly used as a protective structure to contain explosives. This study focused on the response of single walled and sandwich walled cylindrical tubes subjected to an internal explosion. Firstly, real-life detonation experiments were performed to obtain the basic deformation patterns. Finite element (FE) simulations were then conducted in ANSYS and LS-DYNA to obtain the simulated data for deformation pattern. Those simulated results were then validated against the experimentally obtained data. Next, a parametric study was performed in order to obtain the main parameters in an explosive process while keeping the failure strain of the material constant. For single-walled tubes, these were namely found to be the mass of the PE4 explosive used (M), the thickness of the tube wall (h) and the stand-off distance (R). A non-dimensional empirical formula was obtained. Then the response of sandwich-walled tube filled with the closed-cell aluminum foam under PE4 charge was investigated numerically. The numerical results revealed that the deformation or failure, and the energy absorption of the sandwich tubes were significantly affected by the PE4 charge, and also the mass ratio of the tube to the foam. As a first step, a simplified one-dimensional axisymmetric analytical model was presented where the filled foam was assumed to have an initial rigid regime, followed by a perfectly-plastic stage and locking densification (R-PP-L). Comparison with the numerical model gives a fairly good agreement.